An Electrochemically Actuated MEMS Device for Individualized Drug Delivery: an In Vitro Study. Issue 8 (August 2013) - Song, Peiyi; Tng, Danny Jian Hang; Hu, Rui; Lin, Guimiao; Meng, Ellis; Yong, Ken‐Tye
Abstract Individualized disease treatment is a promising branch for future medicine. In this work, we introduce an implantable microelectromechanical system (MEMS) based drug delivery device for programmable drug delivery. An in vitro study on cancer cell treatment has been conducted to demonstrate a proof‐of‐concept that the engineered device is suitable for individualized disease treatment. This is the first study to demonstrate that MEMS drug delivery devices can influence the outcome of cancer drug treatment through the use of individualized disease treatment regimes, where the strategy for drug dosages is tailored according to different individuals. The presented device is electrochemically actuated through a diaphragm membrane and made of polydimethylsiloxane (PDMS) for biocompatibility using simple and cost‐effective microfabrication techniques. Individualized disease treatment was investigated using the in vitro programmed delivery of a chemotherapy drug, doxorubicin, to pancreatic cancer cell cultures. Cultured cell colonies of two pancreatic cancer cell lines (Panc‐1 and MiaPaCa‐2) were treated with three programmed schedules and monitored for 7 days. The result shows that the colony growth has been successfully inhibited for both cell lines among all the three treatment schedules. Also, the different observations between the two cell lines under different schedules reveal that MiaPaCa‐2 cells are more sensitive to the drug applied. These results demonstrate that further development on the device will provide a promising novel platform for individualized disease treatment in future medicine as well as for automatic in vitro assays in drug development industry.